The impact of rapid molecular diagnostic testing for respiratory viruses on outcomes for emergency department patients. Issue 7 (5th March 2019) - Wabe, Nasir; Li, Ling; Lindeman, Robert; Yimsung, Ruth; Dahm, Maria R; Clezy, Kate; McLennan, Susan; Westbrook, Johanna; Georgiou, Andrew
Abstract: Objective: To determine whether rapid polymerase chain reaction (PCR) testing for influenza and respiratory syncytial viruses (RSV) in emergency departments (EDs) is associated with better patient and laboratory outcomes than standard multiplex PCR testing. Design, setting: A before‐and‐after study in four metropolitan EDs in New South Wales. Participants: 1491 consecutive patients tested by standard multiplex PCR during July–December 2016, and 2250 tested by rapid PCR during July–December 2017. Main outcome measures: Hospital admissions; ED length of stay (LOS); test turnaround time; patient receiving test result before leaving the ED; ordering of other laboratory tests. Results: Compared with those tested by standard PCR, fewer patients tested by rapid PCR were admitted to hospital (73.3% v 77.7%; P  < 0.001) and more received their test results before leaving the ED (67.4% v 1.3%; P  < 0.001); the median test turnaround time was also shorter (2.4 h [IQR, 1.6–3.9 h] v 26.7 h [IQR, 21.2–37.8 h]). The proportion of patients admitted to hospital was also lower in the rapid PCR group for both children under 18 (50.6% v 66.6%; P  < 0.001) and patients over 60 years of age (84.3% v 91.8%; P  < 0.001). Significantly fewer blood culture, blood gas, sputum culture, and respiratory bacterial and viral serology tests were ordered for patients tested by rapid PCR. ED LOS was similar for the rapid (7.4 h; IQR, 5.0–12.9 h) and standard PCR groups (6.5 h; IQR, 4.2–11.9 h; P  = 0.27). Conclusion: Rapid PCR testing of ED patients for influenza virus and RSV was associated with better outcomes on a range of indicators, suggesting benefits for patients and the health care system. A formal cost–benefit analysis should be undertaken.